A modelling study of glycolytic oscillations and electrical activity in pancreatic alpha cells - Olivos-Santes, E.; Romero-Campos, H. E.; Dupont, G.; González-Vélez V. (Revista Mexicana de Ingenieria Biomedica, 2019)
Pancreatic alpha and beta cells release the main hormones involved in blood glucose regulation: glucagon and insu- lin, respectively. Based on the observation that metabolic oscillations are related to electrical activity and, in turn, to insulin secretion in beta cells, in the present work we use a mathematical modelling approach to explore the con- tribution of glycolytic oscillations to electrical activity in alpha cells. Due to lack of data about metabolism in alpha cells and taking into account that pancreatic cells comes from a common progenitor, we used a previous model of pancreatic beta cells and focus on the main differences between both cell types. The main finding contrasts with beta cells since electrical activity in alpha cells could be triggered independently of glycolic oscillations. It suggests that alpha cells are stimulated by blood glucose through a different pathway, which is in agreement with the role of alpha cells during hypoglycemia.